Effect of Emotional Intelligence and Organizational Culture on Performance with Organizational Commitment as Mediation - Eric Leon Louhenapessy; Tuty Lindawati (Green Publisher Indonesia, 2022)
Non Educational Permanent Employees are human resources who provide support to the Foundation in carrying out education management with the capacity and capability, this will have a positive impact on the sustainability of the Foundation. This study aims to determine the effect of emotional intelligence and organizational culture on performance with organizational commitment as a mediation for non-educational permanent employees at the Yohannes Gabriel Foundation. This research is a causal research. In this study the method used is a survey, namely by distributing questionnaires to Non-Educational Permanent Employees at the Yohannes Gabriel Foundation. The population in this study were all non-educational permanent employees at the Yohannes Gabriel Foundation. The sample in this study were 60 respondents. Researchers used PLS (Partial Least Square) as an analytical method. The results showed that there was no significant effect of Emotional Intelligence on Organizational Commitment, there was a positive and significant influence of Organizational Culture on Organizational Commitment, there was a positive and significant influence of Organizational Commitment on Performance, there was a positive and significant influence of Emotional Intelligence on Employee Performance, there was a positive and significant influence Organizational Culture has a significant effect on Employee Performance, there is no significant effect of Emotional Intelligence on Employee Performance through Organizational Commitment, and there is a significant influence of Organizational Culture on Employee Performance through Organizational Commitment.